Pathophysiology of severe traumatic brain injury / Fisiopatología de la lesión cerebral traumática severa - University of Campinas, Department of Neurosurgery (Revista Cubana de Medicina Intensiva y Emergencias, 2018)
KEY POINTS Primary Injury: injury for the traumatic event itself, the direct impact in the neural tissue with ischemia, contusion and hemorrhage. Secondary Injury: occurs after the primary injury that starts secondary cellular phenomena in the neural tissue: Early Phase: interruption of the blood flow with hypoxia Intermediary Phase: neuroinflammation, activation of the microglia Late Phase: regeneration and self-repair Cerebral blood flow auto regulation, primary measures to treat ICP elevation and ICP monitoring in severe TBI are also described.